2005
DOI: 10.2134/jeq2004.0466
|View full text |Cite
|
Sign up to set email alerts
|

Can Constructed Wetlands Reduce the Diffuse Phosphorus Loads to Eutrophic Water in Cold Temperate Regions?

Abstract: Construction of wetlands is a possible supplement to best management practices (BMP) at the field level to mitigate phosphorus (P) pollution from agricultural areas. In this paper, annual results from 17 intensively studied wetlands in the cold temperate or boreal climatic zone are reported and analyzed. Surface areas varied from 0.007 to 8.7% of the catchment area. The average total phosphorus (TP) retention varied from 1 to 88%, and the dissolved reactive phosphorus (DRP) retention from -19 to 89%. Retention… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
69
0
3

Year Published

2006
2006
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 108 publications
(73 citation statements)
references
References 31 publications
1
69
0
3
Order By: Relevance
“…Others have suggested smaller, strategically placed features could play a key role (Braskerud et al ., 2005; Ockenden et al ., 2014). However, such work commonly focuses on anthropogenic features with associated construction and maintenance costs (Ockenden et al ., 2012).…”
Section: Discussionmentioning
confidence: 99%
“…Others have suggested smaller, strategically placed features could play a key role (Braskerud et al ., 2005; Ockenden et al ., 2014). However, such work commonly focuses on anthropogenic features with associated construction and maintenance costs (Ockenden et al ., 2012).…”
Section: Discussionmentioning
confidence: 99%
“…Dividing the volume treated (27, Overall, the performance of the IESF in this study (63.9% phosphate and 66.3% total phosphorus load reduction) is comparable to other agricultural treatment practices and studies of IESFs. The IESF captures more phosphorus than constructed wetlands, for both total phosphorus (2-44%, [10][11][12][13][14]) and phosphate (9%, [12]), though the data falls within the upper range reported for a study of 17 intensively studied constructed wetlands (TP = 1-88%; DRP = −19 to 89%, [15]). Laboratory experiments of IESFs in previous studies found an average of 88% phosphate capture with a total treated depth of 200 m [18].…”
Section: Hydraulic and Phosphate Loading Ratementioning
confidence: 45%
“…By comparison, ten Discovery Farms Minnesota (DFM) sites reported total phosphorus loads for the entire 2016 water year ranging from 11.2 to 157 g/ha for The total phosphorus load reduction for each event varied from 42% to 95% with an overall total phosphorus load reduction of 66.3% ± 6.7% (α = 0.05, n = 20). A substantial portion of the influent total phosphorus load (323.6 g, 25%) was contributed by two events: 19 August 2016 (178.3 g) and 15 September 2016 (145.3 g), as shown in Figure 4. These two events contributed approximately 17.8% of the rainfall-induced tile drainage in 2016.…”
Section: Total Phosphorusmentioning
confidence: 99%
“…Through an empirical study, Kovacic et al (2006) determined that if 5% of the Lake Bloomington Watershed (1,112 acres) was converted to constructed wetlands at a cost of $1,500/acre/year (assuming a 50-year operational lifetime and neglecting the cost of land), nitrogen loadings at the watershed outlet would be reduced by 46%.Other studies have also indicated that wetlands make significant improvements in water quality. According to a survey of 17 sites in North America and Northern Europe done by Braskerud et al (2005), constructed wetlands were capable of up to an 89% removal rate for nitrogen. In Illinois, a 37% reduction in total nitrogen was estimated by Kovacic et al (2000) at three sites treating tile drainage water; while a mass percent removal of 39-99% of nitrate was reported by Hey et al (1994) treating stream water from the Des Plaines River.…”
Section: Introductionmentioning
confidence: 99%